Laboratory for primary pharmacological screening for the study of promising biologically active substances among 1,2,4-triazole derivatives - Mykhkailiuk, Ye. O.; Михайлюк, Євгеній Олегович (Запорізький державний медико-фармацевтичний університет, 2023)
The Aim: the primary objective of our research is to identify safe and promising substances among 1,2,4-triazole derivatives, possessing various types of biological activity, for further in-depth study.
Keywords: тези доповідей